Accuracy of multislice computed tomography in the diagnosis of hepatocellular carcinoma in patients with cirrhosis evaluated for liver transplantation - Haberman, Diego (2011)
The presence of hepatocellular carcinoma (HCC) within Milan criteria provides additional points in the MELD (Model for end stage liver disease) system and benefits in the order of organ allocation. The imaging methods play a key role in this process and represent an essential tool in the diagnosis and staging of HCC. OBJECTIVES: 1) To assess the accuracy of dynamic multidetector computed tomography (MDCT) in the diagnosis of HCC in patients with cirrhosis who are listed for liver transplantation. 2) To evaluate the diagnostic performance of TCMD in relation to tumor size. MATERIAL AND METHODS: We retrospectively reviewed the reports of MDCT performed in our institution to 62 patients who were then transplanted The histological analysis of explants was considered as the reference method in the diagnosis of HCC. MDCT studies were performed with dynamic protocol in arterial, portal and late phases. RESULTS: Dynamic MDCT showed a sensitivity of 87.5% and correctly characterized 28 of 35 patients with pathology proved hepatocellular carcinoma. MDCT was negative in 25 of 30 patients without hepatocellular carcinoma in the explanted liver, with a specificity of 83.3%. Nodule by nodule evaluation revealed a sensitivity of 80.3% and a specificity of 72.2%. CONCLUSION: In our center MDCT presented high accuracy in the correct diagnosis of HCC, showing its reliability when requesting additional points for organ allocation.